2007
DOI: 10.1021/np0700772
|View full text |Cite
|
Sign up to set email alerts
|

Antimalarial Linear Lipopeptides from a Panamanian Strain of the Marine Cyanobacterium Lyngbya majuscula

Abstract: As part of the Panama International Cooperative Biodiversity Groups (ICBG) project, two new (2, 4) and two known (1, 3) linear alkynoic lipopeptides have been isolated from a Panamanian strain of the marine cyanobacterium Lyngbya majuscula. Carmabin A (1), dragomabin (2), and dragonamide A (3) showed good antimalarial activity (IC 50 4.3, 6.0, and 7.7 μM, respectively) whereas the non-aromatic analog, dragonamide B (4), was inactive. The planar structures of all four compounds were determined by NMR spectrosco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
108
1
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 147 publications
(116 citation statements)
references
References 22 publications
3
108
1
1
Order By: Relevance
“…Apramides A-B (44A-B) and D-E contained variably methylated 7-octanoic acid termini and had negligible bioactivity [435]. The related planar metabolites dragomabin (44C) [436], carmabin (44D) [437], and dragonamides A-B (44E-F) [436,438] are also known; 44A-C were isolated with 7-alkenoate and 42-keto lipid modifications, respectively. α-Methylation of the fatty amide group was (S) in each case (the original assignment for 44E was corrected by total synthesis).…”
Section: Acetylenic Lipopeptides and Cyclodepsipeptidesmentioning
confidence: 99%
See 1 more Smart Citation
“…Apramides A-B (44A-B) and D-E contained variably methylated 7-octanoic acid termini and had negligible bioactivity [435]. The related planar metabolites dragomabin (44C) [436], carmabin (44D) [437], and dragonamides A-B (44E-F) [436,438] are also known; 44A-C were isolated with 7-alkenoate and 42-keto lipid modifications, respectively. α-Methylation of the fatty amide group was (S) in each case (the original assignment for 44E was corrected by total synthesis).…”
Section: Acetylenic Lipopeptides and Cyclodepsipeptidesmentioning
confidence: 99%
“…α-Methylation of the fatty amide group was (S) in each case (the original assignment for 44E was corrected by total synthesis). Amides 44C-E inhibited the W2 chloroquine-resistant strain of P. falciparum but 44F was inactive, which suggested that an aromatic amino acid was required for antimalarial activity [436].…”
Section: Acetylenic Lipopeptides and Cyclodepsipeptidesmentioning
confidence: 99%
“…These lipopeptides were found to have interesting bioactivities, including, anti-inflammatory, antimalarial properties, antimicrobial, antileishmanial, cytotoxic and neurotoxic activities. [1][2][3][4][5][6][7][8][9] Fellutamides A and B are lipopeptides first isolated from the fish-derived fungus Penicillium fellutanum. Fellutamides exhibit cytotoxic properties, 10 and fellutamide A has been shown to stimulate the synthesis and secretion of nerve growth factor (NGF) in vitro.…”
mentioning
confidence: 99%
“…from coastal regions of Panama. Likewise, crude organic extracts of Lyngbya majuscula from different sites of coastal regions of Panama exhibited promising antiplasmodial activities (IC 50 ¼ 6 and 26 mg mL À1 ) against CQ-resistant P. falciparum (McPhail et al, 2007). It is interesting that, in our study, the organic extract of in vitro grown L. aestuarii CNP 1005 has shown promising antiplasmodial activity against both CQ-sensitive (IC 50 ¼ 18 mg mL À1 ) and resistant strains (IC 50 ¼ 34 mg mL À1 ) of P. falciparum.…”
Section: Discussionmentioning
confidence: 99%
“…More interestingly, marine Moorea producens (earlier known as Lyngbya majuscula Harvey in Hooker ex Gomont) has been found to exhibit potent antimalarial activity against Plasmodium falciparum and a number of antimalarial compounds such as lagunamides (Tripathi et al, 2010a), dragomabin (McPhail et al, 2007), and malyngolide (Gutiérrez et al, 2010) have been isolated from it. Likewise, antimalarial screening of 18 cyanobacterial strains showed that the methylene dichloride extract of Phormidium ectocarpi inhibited the malaria parasite (IC 50 ¼ 2.1 mg mL À1 ) (Papendorf et al, 1998).…”
Section: Introductionmentioning
confidence: 99%